Current status and future perspectives of clinical research in pancreatic cancer: Establishment of evidence by science. (21st September 2021) - Pu, Ning; Yin, Hanlin; Chen, Qiangda; Zhang, Jicheng; Wu, Wenchuan; Lou, Wenhui
Abstract: Pancreatic cancer is one of the most aggressive diseases in the world due to a lack of early detection, leading to an overall 5‐year survival of only 10%. In recent years, clinical trials targeted pancreatic cancer in efforts to improve survival. These studies introduce new technologies, concepts, and evidence which have instilled new optimism for improving prognosis. This review summarizes the current status of the recent (5‐year) clinical trials and describes contemporary research on pancreatic cancer, including surgical technology, diagnostic skills, traditional chemoradiotherapy, neoadjuvant chemotherapy, immunotherapy, targeted therapy, and precision medicine. Then, the future trend and direction of clinical trials on pancreatic cancer are discussed. Abstract : Pu et al. summarized the current status of clinical trials conducted in the past 5 years and described the contemporary research on pancreatic ductal adenocarcinoma. A comprehensive treatment strategy focused on multiple aspects may provide the best synergism and should be advocated to improve the prognoses of pancreatic ductal adenocarcinoma.